2022
DOI: 10.3390/ijms232012589
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Anticancer and Antitubercular Properties of New Chalcones and Their Nitrogen-Containing Five-Membered Heterocyclic Hybrids Bearing Sulfonamide Moiety

Abstract: A new series of sulfonamides, 8a-b, 10, 12, and 14a-b, were synthesized by N-sulfonation reaction with sulfonyl chlorides 6a-b. Five new series of chalcone-sulfonamide hybrids (16-20)a-f were prepared via Claisen–Schmidt condensation of the newly obtained sulfonamides with aromatic aldehydes 15a-f in basic medium. Chalcones substituted with chlorine at position 4 of each series were used as precursors for the generation of their five-membered heterocyclic pyrazoline (22-23)a-d, (24-25)a-b and carbothioamide 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…When compared to other reported chalcones tested on different melanoma cell lines, we found that compound 12 is two times more active than those of the ethoxy-chalcones class, studied by Harshitha et al [36], where the best derivative showed an IC 50 value of 53.47 µM for A-375 metastatic melanoma cell line. On the other hand, compound 12 was found to be less active than the synthesized chalcone-sulfonamide hybrids reported by Castaño et al [37], most of them possessing activities against LOX IMVI melanoma cell line, with IC 50 values between 0.34 and 0.54 µM.…”
Section: Antimelanoma Activitiesmentioning
confidence: 61%
“…When compared to other reported chalcones tested on different melanoma cell lines, we found that compound 12 is two times more active than those of the ethoxy-chalcones class, studied by Harshitha et al [36], where the best derivative showed an IC 50 value of 53.47 µM for A-375 metastatic melanoma cell line. On the other hand, compound 12 was found to be less active than the synthesized chalcone-sulfonamide hybrids reported by Castaño et al [37], most of them possessing activities against LOX IMVI melanoma cell line, with IC 50 values between 0.34 and 0.54 µM.…”
Section: Antimelanoma Activitiesmentioning
confidence: 61%
“…Castano and collaborators (2022) [ 74 ], synthesized chalcone-sulfonamide hybrids. Since the compound ( 67 ) ( Figure 13 ) presented the best inhibition profile for LOX IMVI (melanoma) with IC50 = 0.34 µM, it also showed good results for MCF7 and MDA-MB-468 (breast cancer) with IC50 values of 0.97 and 1.20 µM, respectively; K-562 (leukemia) with IC50 = 1.50 µM, and HCT-116 (colon cancer) with IC50 = 1.49 µM.…”
Section: Chalcones With Anticancer Activitymentioning
confidence: 99%
“…Scientific groups have reported on the successful implementation of the hybrid pharmacophore concept, which is performed through combining heterocycles with recognized active groups like sulfonamides [ 42 , 43 ]. Hybridized heterocycles with sulfonamides were successfully applied in the reported literature as seen in the interconnection between phthalazinone derivatives and sulfonamides as sulfadiazine and sulfathiazole, which was a successful strategy to synthesize broad-spectrum antibacterial compounds [ 28 ].…”
Section: Introductionmentioning
confidence: 99%